The role of government funding in the effort to enhance organisational performance: A conceptual framework - Khalid, Nadeem; Ismail, Noor Azizi; Syed Ismail, Syed Soffian; Abdul Malek, Marlin Marissa (Othman Yeop Abdullah (OYA) Graduate School of Business, Universiti Utara Malaysia, 2016)
The present article seeks to advance the theoretical knowledge of entrepreneurship by reviewing and synthesizing available research into a conceptual framework that explains the process of how higher education institutes can achieve sustainable performance by adopting entrepreneurial mind set. The framework identifies impact of public entrepreneurial factors, e entrepreneurial training on innovation and entrepreneurial orientation on organisational performance of Higher Education Institutions.This research also proposes the moderating effect of government funding to enhance the organisational performance in general and university performance in particular.